Gambaran Negative Automatic Thoughts pada Remaja Korban Bullying di Sekolah Menengah Pertama Kota Bandung - Andhita Nurul Khasanah; Temi Damayanti; Dwi Agustin Nuriani Sirodj (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
This research aimed to obtain a description explanation about negative automatic thoughts that appear on Bandung junior high school students who are bullied. The research also described the automatic negative thoughts that was based on factors affected by bullying (from CATS questionnaire). The research involved 1261 samples of the students of 5 junior high school in Bandung. Data were analyzed using descriptive statistic analysis. The results showed as many as 48 students belonging to students who experience the action of bullying with high frequency and as many as 333 students experience the act of bullying in the medium frequency. Then, based on the results of CATS questionnaires, about 8.3% of students, show that they had higher frequency the occurrence of negative automatic thoughts. It means they had a negative beliefs scheme and often experience helplessness in their daily lives. The factor analysis showed that social threat was the most contributive factor in generating negative automatic thoughts.